When crizotinib-induced bradycardia becomes symptomatic: role of concomitant drugs. Issue 7 (July 2015) - Gallucci, Giuseppina; Tartarone, Alfredo; Lombardi, Lucia; Aieta, Michele
<x xml:space="preserve">Abstract</x> Crizotinib is an orally active multi-target tyrosine kinase inhibitor which is the standard of care in patients with anaplastic lymphoma kinase translocated non-small-cell lung cancer. Common adverse events in clinical trials with crizotinib included visual disorders, nausea–vomiting, diarrhea and elevated transaminases. Less common toxicities are emerging, such as bradycardia and QT interval prolongation. We report on a case of a presyncopal episode which occurred under crizotinib and metoclopramide treatment.